(untitled) (Intent Research Scientific Journal, 2023)
The article says that the result of the classification of categories of contrastivity (contrasts) in general, and at individual levels of the language system, it should be the development of optimal recommendations to overcome the differences between the native and the studied languages, i.e. to the practical mastery of the language being studied.